Social Network Sites Engagement in the Job Search Process among Women in Poland - Ewa Prymon-Rys (Communications of International Proceedings, 2021)
Many recent studies have documented the influence of social media usage on consumer purchasing decisions. However, less is known about how newer forms of media such as social networking sites influence more significant decisions about choosing a new employer and job search. The present study aimed to examine how Polish women use social media in the process of searching for a job and evaluating prospective employers. 795 women aged 18–35 years were asked about their social media use. Respondents then described their experiences with recruitment processes including social media usage and their satisfaction with their present job position. In the research an internet survey approach was used. These findings have implications for HR practitioners and marketers responsible for an employer branding strategy to develop most successful social media communication programs with women as new employees in recruitment processes.
Keywords: Social Network Sites; Job Search; Women; Employer Brand.